Algorithmic short-selling with Python : refine your algorithmic trading edge, consistently generate investment ideas, and build a robust long/short product /: refine your algorithmic trading edge, consistently generate investment ideas, and build a robust long/short product. (2021) - Bernut, Laurent
No abstract available